Stochastic discounting and the transmission of money supply shocks - Ivan Jaccard (European Central Bank (ECB), 2018)
This paper studies the effects of money supply shocks in a general equilibrium model that reproduces a term premium of the magnitude observed in the data. In an environment where financial frictions are the main source of monetary non-neutrality, I find that money supply shocks are less effective at stimulating inflation in recessions than in expansions. In terms of quantitative magnitude, the impact effect on inflation of a money supply shock is about half as large during recessions than during booms. This state dependence is essentially due to the time-variation in stochastic discounting that is needed to match the data.
Keywords: E31; E44; E58; 330; Bond premium puzzle; financial frictions; time-varying risk aversion; euro zone economy